Changes in lymphocyte subsets pre- and post-particle radiotherapy in head and neck bone and soft tissue tumors - Zhang, Haojiong; Gao, Jing; Hu, Jiyi; Hu, Weixu; Huang, Qingting; Kong, Lin (Frontiers in Oncology, 2025)
PurposeBone and soft tissue tumors present unique therapeutic challenges due to their heterogeneity and poor prognosis to standard treatments. Particle therapy offers improved dose distribution and potentially higher relative biological effectiveness, however, its immunological effects in patients remain poorly understood. Investigating peripheral immune cell changes could offer valuable insights for integrating immunotherapies and optimizing treatment outcomes.MethodsIn this observational study, we enrolled 12 patients with head and neck bone and soft tissue tumors treated at our center between November 1, 2022, and November 1, 2024. Treatment modalities included proton or carbon-ion radiotherapy, with or without chemotherapy, targeted therapy, or immunotherapy. Peripheral blood samples were collected both before and after the completion of radiotherapy. Hematologic assessments were conducted, including total lymphocyte counts and immunophenotyping of CD3+, CD4+, CD8+, and other lymphocyte subsets. Statistical analyses, including paired Student’s t-test, Wilcoxon signed-rank tests and univariate analysis, were performed to investigate associations between lymphocyte changes and clinical factors.ResultsMinor reductions were noted in CD3+ and CD4+ T cell subsets, accompanied by a small increase in CD3+CD4–CD8– subsets. Even after excluding the patient who received immunotherapy, the observed trend in lymphocyte counts and subset changes remained consistent. This finding suggests that, compared with conventional photon radiotherapy, particle therapy may better preserve immune function. Remarkably, all patients were alive and showed no evidence of disease progression during the study period.ConclusionParticle therapy in patients with head and neck bone and soft tissue tumors induces modest immunological alterations, suggesting it may preserve immune function more effectively than conventional photon radiotherapy. These preliminary findings from our small cohort support further research into combining particle therapy with immunomodulatory strategies, potentially enhancing clinical outcomes and expanding therapeutic options for these challenging malignancies.